On the Demographic and Selective Forces Shaping Patterns of Human Cytomegalovirus Variation within Hosts - Andrew M. Sackman; Susanne P. Pfeifer; Timothy F. Kowalik; Jeffrey D. Jensen (Pathogens, 2018)
Human cytomegalovirus (HCMV) is a member of the β -herpesvirus subfamily within Herpesviridae that is nearly ubiquitous in human populations, and infection generally results only in mild symptoms. However, symptoms can be severe in immunonaive individuals, and transplacental congenital infection of HCMV can result in serious neurological sequelae. Recent work has revealed much about the demographic and selective forces shaping the evolution of congenitally transmitted HCMV both on the level of hosts and within host compartments, providing insight into the dynamics of congenital infection, reinfection, and evolution of HCMV with important implications for the development of effective treatments and vaccines.